2010
DOI: 10.1080/17458080903583964
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced transdermal delivery of carvedilol using nanoemulsion as a vehicle

Abstract: The aim of the present study was to develop nanoemulsion as a possible vehicle for enhanced transdermal penetration of carvedilol (CVD). For screening of nanoemulsion components, solubility of CVD in oils, surfactants and co-surfactants was determined. Various surfactants and co-surfactants were screened for their ability to nanoemulsify the selected oily phases. The obtained results indicated that Acconon CC6Õ had shown good nanoemulsification efficiency (minimum surfactant required S min ¼ 46.52% w/w) among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In a comparative study between the selected cosurfactants, Tween 20 showed larger self-emulsification region than PEG 600, due its hydrophilic nature. Higher hydrophilicity property favors faster emulsification of the oil-surfactant mixture in contact with water (28). Based on the various combinations, Capmul MCM, Labrasol, and Tween 20 (1:1) were selected for formulation development, as the above S mix ratio showed highest area for nanoemulsion formation.…”
Section: Construction Of Pseudoternary Phase Diagramsmentioning
confidence: 99%
“…In a comparative study between the selected cosurfactants, Tween 20 showed larger self-emulsification region than PEG 600, due its hydrophilic nature. Higher hydrophilicity property favors faster emulsification of the oil-surfactant mixture in contact with water (28). Based on the various combinations, Capmul MCM, Labrasol, and Tween 20 (1:1) were selected for formulation development, as the above S mix ratio showed highest area for nanoemulsion formation.…”
Section: Construction Of Pseudoternary Phase Diagramsmentioning
confidence: 99%
“…In the last few years, several transdermal patches have been developed for the delivery of carvedilol through the skin. Carvedilol has been delivered through various transdermal delivery systems, such as nanoemulsions [ 9 ], lipid based nanoparticles [ 10 ], and matrix based systems [ 11 ]. A matrix based transdermal patch showed enhanced bioavailability of carvedilol by 72%, as compared to the oral route [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Figure 2, it was known that ethanol was the best cosurfactant in producing ginger oil nanoemulsion due to its translucent visualization and highest percentage transmittance. Furthermore, the higher the percentage transmittance, the smaller the particle size [31][32]. Combination of tween 80 and propylene glycol resulted a turbid nanoemulsion with percentage transmittance less than 90%.…”
Section: Preparation Of Nanoemulsionsmentioning
confidence: 99%